Transformasi Digital: Mengoptimalkan Website Desa Made Jombang sebagai Media Informasi dan Layanan Publik - Hidayat, Rohmat; Stianto, Mitayakuna; Mardiani, Novita; Mahmud, Mohammad Ikhfian; Bachtiar, Tegar Puji; Febriana, Khoirul Annisa; Turohmah, Latifah; Pusponegoro, Raden Issaga (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The need for a village website is increasingly urgent in the digital era, especially as a tool to manage various aspects of village life more effectively. As a government unit that plays an important role in serving the community, villages need a platform that is transparent, easily accessible, and reliable. This community service program aims to optimize the website of Made Village, Jombang, so that it can function as an effective and efficient information system. Through a series of activities such as interface design improvement, SEO (Search Engine Optimization) optimization, and training for website managers, the Made Village website is expected to become a more attractive, informative, and useful promotional media. The approach used in this program is *Community Based Participatory Research* (CBPR), which emphasizes close collaboration between researchers and village communities. This approach involves the active participation of village communities in every stage of activities, from planning to evaluation, so that they have a strong sense of ownership of the results. This participation not only strengthens collaboration, but also encourages communities to be more involved in their village's digital transformation. The results of the program showed an increase in the number of website visitors and user interactions. In addition, this program has succeeded in increasing community awareness of the importance of information technology. It is hoped that the optimization of the village website will not only encourage local economic development through the promotion of products and tourism, but also strengthen the identity of the Made Village community. Through a participatory approach, this program contributes to broader and sustainable social change